Preliminary evaluation of a salivary urea test strip method for use in dogs. (10th August 2019) - Sanchini, Lucia; Hare, Cassia H. Z.; Restif, Olivier; Williams, Tim L.
Abstract: Background: Salivary urea concentrations correlate with serum urea concentrations in dogs and humans. Salivary urea concentrations can now be determined semi‐quantitatively using a salivary urea test strip method that has been validated for use in humans. Objectives: We aimed to evaluate the repeatability of the salivary urea test strip score, and the correlation between the salivary urea test strip scores and serum urea concentrations in dogs. Methods: Intra‐run and inter‐run variabilities were determined (n = 10 in triplicate). Correlations between salivary urea test strip scores and serum urea concentrations in dogs were assessed using the Spearman's correlation coefficient. Receiver operator curve analysis was used to evaluate the diagnostic performance of the salivary urea test strip score to identify dogs with serum urea concentration >7.4 mmol/L (upper limit of laboratory RI). Results: The intra‐run repeatability was good (28/30 concordant results) whereas the inter‐run repeatability was moderate (23/30 concordant results). Salivary and serum urea concentrations showed a moderately positive correlation ( r s  = .63, n = 33; P  < .0001). A salivary urea test strip score ≥4 was 57% sensitive and 96% specific for detecting a serum urea concentration >7.4 mmol/L. Conclusions: Uremia can be detected using salivary urea test strips in dogs. Based on our preliminary data, salivary urea test strip scores of 1 or 2 might exclude clinically relevant uremia in most cases; however, it is recommended that the salivary urea test be repeated in dogs with a test strip score of 3. Dogs with a salivary urea test strip score of ≥4 would likely require additional investigations.